WRITTEN CORRECTIVE FEEDBACK IN WRITING SKILL: A BRIEF REVIEW - Setiyowati Setiyowati; Hanna Sundari (INFERENCE: Journal of English Language Teaching, 2021)
The study presented here includes collectively selected research papers that emphasize written corrective feedback, particularly Direct Written Corrective Feedback and Indirect Written Corrective Feedback. Writing is considered the most challenging task for students because writing needs the student's creativity to form ideas of their minds into a form of a text. Some difficulties that EFL students in writing usually find are the lack of the knowledge to choose the appropriate vocabulary, and they also have some problems in grammar and syntax. To overcome these, Written Corrective Feedback (WCF) has been used widely to show students grammatical errors in EFL students' writing works and help EFL students minimize their errors. The Written Corrective Feedback also shows students' performance in enhancing their writing accuracy. Five selected research papers have been selected to give some enlightenment about the effectiveness of Written Corrective Feedback. The feedback was given by EFL teachers and lecturers who teach in Indonesia, China, Iran, Malaysia, and Thailand. The method that is used in this literature review study is thematic analysis design. These are divided into five themes. The themes are Participants, Treatment, The Treatment Length, Instruments and Writing Prompt, and The Effectiveness of The Written Corrective Feedback. The findings reveal various results in the use of Direct Written Corrective Feedback and Indirect Written Corrective Feedback.